Prognozy długookresowe dla wartości zagrożonej Value at Risk w ocenie ryzyka inwestowania w akcje - Pisula, Tomasz; Mentel, Grzegorz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
There is a growing demand for models which enable to measure and assess risk in long run horizons (sometimes more than 2 years). The practical demand for such models is required by the institutions which manage the investment and retirement funds. In the paper the theoretical aspects of risk assessment methodology with the use of Value at Risk (VaR) have been presented. In this method in order to estimate the predicted long run VaR limits the hybrid model, which is the optimum mixture of random walk and mean reversion has been used. The application of the presented methodology has been exemplified by the estimation of long run predictions for VaR limits for share prices. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 308-315